Text and text processing - Denhiere, Guy; Rossi, Jean-Pierre (Advances in psychology (Amsterdam, Netherlands), 1991)
The book presents the state-of-the-art in major aspects of text analysis and cognitive text processing by some of the most well-known European and American researchers in the field of text-linguistics and cognitive psychology. Comprehensive views and new perspectives are proposed in the following topics: cognitive and metacognitive aspects of text processing, structures and processes involved in the construction of multi-level semantic representations in relation with text and reader characteristics, achievement of local and global coherence of meaning during reading and comprehension, assessment of knowledge, knowledge acquisition of concepts and complex systems by text, and cognitive and metacognitive aspects of text production.